Testing the oceanic dispersal potential of Caribbean fleshy-fruited plants - Seokmin Kim; Sofany Montoya; Fabio L. Tarazona-Tubens; Christina Chavez; Joanna Tucker Lima; Donald Olson; Christopher Searcy (PLoS ONE, 2026)
Thalassochory, or dispersal by ocean currents, shapes island biogeographical processes. However, the potential of fleshy-fruited plants to utilize this dispersal method is understudied. We selected 14 fleshy-fruited species found in coastal Caribbean plant communities and assessed their thalassochoric dispersal potential by measuring the period during which they could both float and remain viable in saltwater. We then determined the thalassochoric connectivity between 44 Caribbean islands by analyzing the paths of 1198 drifter buoys that passed through the Caribbean between 1991 and 2019. We found a significant, positive trend for fruits with greater thalassochoric dispersal potential to be found on more islands and significant variation in the floating potential of Caribbean fleshy-fruited plants (0–90 + days), with the species with the greatest floating potential ( Chrysobalanus icaco ) feasibly being able to disperse viable seeds between the most geographically distant (2600 km) pair of islands in the Caribbean. However, we could not tie thalassochoric connectivity to either individual species distributions or community composition across our 14 fleshy-fruited species. Geographic distance, the isolation metric traditionally used in island biogeography studies, could not explain distribution or community patterns either, while human usage was identified as an alternative significant predictor of species range size. Our results thus illustrate the challenges associated with identifying drivers of distribution patterns across the Caribbean archipelagos. While we assert that future studies, such as those examining genetic connectivity of plant populations in the context of thalassochoric connectivity, are needed, this study serves as a crucial first step in understanding the role of sea currents in the distribution of fleshy-fruited plants.